Making the Legal World: Normativity and International Computational Law - van den Hoven, Émilie (Communitas, 2022)
The attention devoted to so-called “computational law” has grown exponentially over recent years. However, to date, there has comparatively been much less discussion about the use of data-driven methods, including artificial intelligence, in the processes and institutions of international law. This paper discusses this in terms of “international computational law” and examines what the implications could be if the normativity of technology encounters the normativity of law in the context of international law-making processes. Will it be a smooth and fortuitous alignment or a surreptitious undermining of accepted legal practices—or something in between? To critically engage with this question, a closer look is had at current and future data-driven practices in international treaty-making, the identification of international custom and international institutional lawmaking. Consequently, three types of normativity (i.e., international legal, legal and technological) are analyzed in this context, building on an analysis of the fundamental underlying structure of law. This analysis of normativity leads to the conclusion that we cannot simply assume that these types of normativity will align organically when it comes to our international legal system. I therefore conclude this article by suggesting that more research should be conducted into an adequate conception of “international legal protection by design” to thoughtfully consider how to safeguard legal protection in an increasingly computationalized international legal order. This will be crucial if we want to ensure that international law in the algorithmic age affords us legal protection and that we design our global order with thoughtfulness, rather than encodethoughtlessness.